IMPLEMENTASI HUKUM TINDAK PIDANA KORUPSI DENGAN KERUGIAN KEUANGAN NEGARA DIBAWAH 50 JUTA RUPIAH - Tri Lestari; Burham Pranawa; Tegar Harbriyana Putra (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2025)
The increasing number of corruption crimes in Indonesia has caused significant losses to state finances, including in cases with losses below 50 million rupiah. The legal handling based on Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption. However, in practice, minor corruption cases are often resolved through a restorative justice approach, as regulated by the Attorney General’s Circular and Prosecutor Regulation No. 15 of 2020. This study aims to examine the implementation of law in handling corruption cases involving state losses below 50 million rupiah, particularly from the perspective of restorative justice. The research method is normative juridical with a descriptive qualitative approach, relying on secondary data and interviews with the Boyolali District Attorney’s Office. The results indicate that restorative justice is applied to achieve efficiency and effectiveness, provided that the perpetrator is a first-time offender and the loss has been fully returned. The study concludes that while restorative justice in small-scale corruption aligns with legal efficiency, it remains controversial due to its potential contradiction with the principles of the Anti-Corruption Law.